2010
DOI: 10.1007/s10773-010-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Energy of Charged Black Holes in Generalized Dilaton-Axion Gravity

Abstract: In this paper we calculate the energy distribution of some charged black holes in generalized dilaton-axion gravity. The solutions correspond to charged black holes arising in a Kalb-Ramond-dilaton background and some existing non-rotating black hole solutions are recovered in special cases. We focus our study to asymptotically flat and asymptotically non-flat types of solutions and resort for this purpose to the Møller prescription. Various aspects of energy are also analyzed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…In another, the symmetric pseudotensor of Landau-Lifshitz was used [30]. Some works calculated the total energy of certain anisotropic Bianchi models using different pseudotensors, leading to similar results [32,33,34]. More recently Faraoni and Cooperstock [35], in support of Cooperstock's proposal that gravitational energy vanishes in the vacuum, argued (with the aid of a nonminimally coupled scalar source) that the open, or critically open FLRW universes-as well as Bianchi models evolving into de Sitter spacetimes-also have zero total energy.…”
Section: Introductionmentioning
confidence: 99%
“…In another, the symmetric pseudotensor of Landau-Lifshitz was used [30]. Some works calculated the total energy of certain anisotropic Bianchi models using different pseudotensors, leading to similar results [32,33,34]. More recently Faraoni and Cooperstock [35], in support of Cooperstock's proposal that gravitational energy vanishes in the vacuum, argued (with the aid of a nonminimally coupled scalar source) that the open, or critically open FLRW universes-as well as Bianchi models evolving into de Sitter spacetimes-also have zero total energy.…”
Section: Introductionmentioning
confidence: 99%
“…where the antisymmetric super-potential λ να μ is λ να μ = √ −g[g μβ,γ − g μγ ,β ]g νγ g αβ (18) and M 0 0 is the energy density and M 0 α are the momentum density components. Using the metric in (2), we have found the required components of λ να μ (18);…”
Section: Some Energy Momentum Distributions Of Textures In Grmentioning
confidence: 99%
“…Various authors have tried to purpose energy-momentum problem using the different metrics and different energy-momentum distributions and they obtained some interesting results in general relativity and teleparallel gravity [10,[13][14][15][16][17][18][19][20][21][22]. According to Xulu [23] Virbhadra and his collaborators have showed that different energy-momentum complexes give same and reasonable results for a given space-time [10,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…12 Later, energy and momentum of various spacetimes were calculated using these prescriptions. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] It was displayed that Einstein, Tolman and Landau-Lifshitz energy distributions of Kerr-Newman spacetime give the same results. 13,14 Therefore, it was proved that Einstein, Landau-Lifsitz, Papapetrou and Weinberg energy distributions for all Kerr-Schild class spacetimes have the same results.…”
Section: Introductionmentioning
confidence: 99%